A CONCEPTUAL SYSTEM DYNAMIC MODEL TO DESCRIBE THE IMPACTS OF CRITICAL WEATHER CONDITIONS IN MEGAPROJECT CONSTRUCTION - P. Boateng; Z Chen; S Ogunlana (Journal of Construction Project Management and Innovation)
In Africa, critical weather conditions (CWCs) such as snow, heat waves, harmattan and storms are increasing in frequency and severity. The ability of players in the construction industry to plan against such CWCs and cope with their immediate impact on construction activities is critical to the contractor, client and the community that is affected. As part of a funded research scheme by the Heriot Watt University in Edinburgh, UK and the European Cooperation in Science and Technology (ECOST), this paper aims to introduce a system dynamic (SD) model to describe the impacts of critical weather conditions in megaproject construction for more accurate construction planning against project delays and cost overrun at the strategic level of megaproject management. The SD methods have been used extensively over the last 35 years on complex projects and have proven track records of project management performance in project lifecycle. The SD approach to megaprojects construction planning is first based on extensive literature review into current research practice in mega construction projects in Africa in incorporation with authors’ experience related to megaproject management and research across the world. An experimental SD model is then illustrated for the OR Tambo International Airport (ORTIA) project in South Africa. The paper further discusses the use of such a SD model for better understanding of the impacts of critical weather conditions and to improve accuracy of construction planning in megaprojects management in Africa.